2016
DOI: 10.20471/acc.2016.55.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Insight and Self-Stigma in Patients With Schizophrenia

Abstract: SUMMARY -Poor insight and high level of self-stigma are often present among patients with schizophrenia and are related to poorer treatment adherence, poorer social function and rehabilitation, aggressive behavior, higher level of depression, social anxiety, lower quality of life and selfesteem. Reports on a relationship between insight and stigma are controversial. We examined the relationship of the level of insight and self-stigma in a sample of 149 patients with schizophrenia. Insight was measured with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…As reviewed above, stigma may result in insight leading to despair, and individuals may consider a meaningful life no longer a viable possibility 39,81 . Other studies have also found a direct link between insight and stigma 148 , though others have failed to replicate that 149 .…”
Section: Social and Political Factors As A Root Of Poor Insightmentioning
confidence: 97%
“…As reviewed above, stigma may result in insight leading to despair, and individuals may consider a meaningful life no longer a viable possibility 39,81 . Other studies have also found a direct link between insight and stigma 148 , though others have failed to replicate that 149 .…”
Section: Social and Political Factors As A Root Of Poor Insightmentioning
confidence: 97%
“…Internalized stigmatization may cause schizophrenic patients to restrict their interaction with society, detach themselves from social interactions and experience feelings such as anxiety, shame, lack of self-confidence, helplessness, and weakness. Patients face many adverse effects, such as reduced self-esteem, unemployment, income loss (Omori et al, 2014; Vidovic et al, 2016; Bukhari et al, 2019). Internalized stigmatization prevents the help seeking behaviors of the patients with schizophrenia and their compliance with psychosocial treatment, poses a risk for hospitalization and may negatively affect the recovery (Wahl, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The experienced stigma is related to the emotional experience of discrimination. The self-stigma is accompanied by a loss of positive beliefs about themselves, a decrease in self-esteem and self-confidence, and poorer insight among the individuals with psychoses 10,1216…”
Section: Introductionmentioning
confidence: 99%